New Treatments for Cutaneous Metastatic Melanoma: MAPK Pathway-Targeted and Immune Based Therapies - Ranchon, F.; Boespflug, A.; Rioufol, C.; Schwiertz, V.; Thomas, L.; Dalle, S. (Anti-Cancer Agents in Medicinal Chemistry, 2015)
Increasing knowledge on cellular biology has permitted rapid changes in the treatment of metastatic melanoma. Until 2011, dacarbazine was the gold standard treatment at our disposal. In 2011 the treatment landscape changed dramatically with the approval by the FDA of ipilimumab and vemurafenib. These drugs use two new therapeutic approaches: immunomodulation and the targeting of mutated cellular pathways in tumor cells. These two drugs, used as single agents have shown important increases in overall survival, unseen before in patients with advanced melanoma, but are limited by their toxicities and the appearance of acquired resistances. In this article, we review new therapeutic options in pathway-targeted –with the arrival of MEK inhibitors - and immune based melanoma therapies –with the arrival of anti-PD1 and anti-PDL1- as well as new therapeutic strategies developed to overcome acquired resistance and diminish drug toxicities.
Keywords: BRAF inhibitors